PESO PREGESTACIONAL Y GANANCIA DE PESO GESTACIONAL ASOCIADOS ACONSECUENCIAS MATERNO PERINATALES EN UNA ZONA RURAL DE MÉXICO - Castro Luna, Diana Isabel (2025)
Introduction. Pre-pregnancy weight and excessive gestational weight gain (EGWG) are risk factors for complications in both the mother and her newborn. Objective. To assess the association between pre-pregnancy weight and EGWG with maternal and neonatal complications in a rural area of Mexico. Methods. A prospective cohort study was conducted including 564 pregnant women with singleton pregnancies. Participants were examined during an initial visit at 8–10 weeks and again between 37 and 39 weeks of gestation to evaluate perinatal outcomes. Pre-pregnancy weight and maternal weight gain were categorized according to the guidelines of the Institute of Medicine (USA). Maternal and neonatal complications assessed included: preeclampsia, gestational diabetes, cesarean delivery, labor complications, preterm birth, small for gestational age (SGA), and large for gestational age (LGA). Multiple regression models were applied to examine the independent effects of pre-pregnancy body mass index and EGWG on maternal and perinatal complications. Results. Pre-pregnancy obesity significantly increased the risk of maternal preeclampsia and gestational diabetes (RR 3.1 and 3.3, respectively). In newborns, pre-pregnancy obesity was associated with a relative risk of 2.3 for LGA. In addition, EGWG increased the likelihood of cesarean delivery by 2.5 times and of LGA by 2.4 times. Conclusions. The study found that pre-pregnancy obesity and excessive gestational weight gain are associated with increased risk of various maternal and neonatal complications in a rural population.